2015
DOI: 10.1371/journal.pone.0126864
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Disulfide Bridges to the Thermostability of a Type A Feruloyl Esterase from Aspergillus usamii

Abstract: The contribution of disulfide bridges to the thermostability of a type A feruloyl esterase (AuFaeA) from Aspergillus usamii E001 was studied by introducing an extra disulfide bridge or eliminating a native one from the enzyme. MODIP and DbD, two computational tools that can predict the possible disulfide bridges in proteins for thermostability improvement, and molecular dynamics (MD) simulations were used to design the extra disulfide bridge. One residue pair A126-N152 was chosen, and the respective amino acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…Here we show that this same region can be cross-linked with a long disulfide bond, which results in a 9°C increase in thermal stability. A survey of the literature reveals that most engineered cysteine disulfides give a Tm increase around 5°C, although there are a few cases where a more than 10°C increase in Tm is observed (27)(28)(29)(30)(31)(32)(33)(34)(35)(36). Interestingly, in work related to that described here, Xiang et al (13) demonstrated that halogen-containing NCAAs with relatively long side chains are capable of forming a covalent linkages with a Cys residue and showed that they improved the thermal stability of an affibody by 13°C in vitro.…”
Section: Discussionmentioning
confidence: 73%
“…Here we show that this same region can be cross-linked with a long disulfide bond, which results in a 9°C increase in thermal stability. A survey of the literature reveals that most engineered cysteine disulfides give a Tm increase around 5°C, although there are a few cases where a more than 10°C increase in Tm is observed (27)(28)(29)(30)(31)(32)(33)(34)(35)(36). Interestingly, in work related to that described here, Xiang et al (13) demonstrated that halogen-containing NCAAs with relatively long side chains are capable of forming a covalent linkages with a Cys residue and showed that they improved the thermal stability of an affibody by 13°C in vitro.…”
Section: Discussionmentioning
confidence: 73%
“…The introduction of disulfide bonds in protein structure is considered as a common strategy to improve the thermostability of industrial enzymes [ 36 38 ], however, incorrect design of disulfide bonds may also reduce the catalytic activity and thermostability [ 39 41 ]. A careful selection of the residue pairs in enzyme structure for disulfide bonds engineering was required.…”
Section: Discussionmentioning
confidence: 99%
“…Considering also the importance of disulphide bonds for the maintenance of enzyme conformation (considering in this case plasma esterases) and the impact of heat on disulphide bonds, three aliquots of QCs that underwent thermal inactivation were then kept for 24 h on the benchtop at RT and finally compared with freshly extracted QCs. 22,23…”
Section: Recovery (Rec) and Extraction Efficiency (Ee)mentioning
confidence: 99%